2015
DOI: 10.1016/j.diabet.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin 1 affects leptin levels, food intake and weight gain in normal-weight, but not obese, db/db mice

Abstract: Aim. -Studies in vitro have highlighted the potential involvement of neuregulin 1 (NRG1) in the regulation of energy metabolism. This effect has also been suggested in vivo, as intracerebroventricular injection of NRG1 reduces food intakes and weight gain in rodents. Thus, it was hypothesised that NRG1 might affect serum leptin levels in mice.Methods. -Weight, food intakes, energy expenditure, spontaneous physical activity and serum leptin levels were evaluated in normal-weight C57BL/6JRJ mice following intrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 17 publications
2
32
0
Order By: Relevance
“…Nrg1 mediates cell-cell signaling and plays a critical role in growth and development of multiple organ systems. ICV injection of Nrg1 leads to increased food intake and weight gain in rodents (Ennequin et al 2015) and a recent study has demonstrated positive metabolic effect of Nrg1 on multiple metabolic parameters, including body weight ). In addition, Nrg1 has been associated with BMI in a Korean population (Lee et al 2016),…”
Section: Discussionmentioning
confidence: 99%
“…Nrg1 mediates cell-cell signaling and plays a critical role in growth and development of multiple organ systems. ICV injection of Nrg1 leads to increased food intake and weight gain in rodents (Ennequin et al 2015) and a recent study has demonstrated positive metabolic effect of Nrg1 on multiple metabolic parameters, including body weight ). In addition, Nrg1 has been associated with BMI in a Korean population (Lee et al 2016),…”
Section: Discussionmentioning
confidence: 99%
“…The identification of NRG1 as a key regulator of adipose expansion may provide a novel therapy for obesity. Wild-type mice treated with injections of recombinant NRG1 display metabolic benefits including lowered bodyweight and reduction in percent body fat relative to controls [33] . NRG1 also improved cardiovascular function and attenuated nephropathy in an apoE mutant mouse model [34] .…”
Section: Discussionmentioning
confidence: 99%
“…When NRG1 was used in clinical trials for human heart failure [31,32] no effect on bodyweight was noted; however, the human therapies were brief, 10 -11 days, whereas the mouse studies took 8 weeks. Despite multiple studies of systemic administration of recombinant NRG1 in rodents, all of which demonstrated positive metabolic effects [33][34][35][36][37] , no study has examined its role in adipose expansion directly. This is even more surprising given that NRG1 administration in mice caused a dramatic spike in leptin, an adipocyte-secreted hormone [33] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations